ANALISIS PENAWARAN DAN PERMINTAAN UBI KAYU DI INDONESIA - , Tatang Suryadi, SP.,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to find out the condition of productivity production and cassava land area in Indonesia as well as its projection, to find out factors affecting demand and supply of cassava for its agroindustry in Indonesia. Time data series were used between 1971 and 2009. Secondary data was used which was Indonesian and worldâs cassava, taken primarily from Indonesia and FAO. Table analysis, projection method as well as regression analysis were used for its data analysis method.Research findings show that cassava production in Indonesia until 2009 comprised 22,039 (million tonnes), with its land area 1,176 (million hectares) having productivity of 187,5 (quintalls/hectare). It is projected that in 2020 its production will reach 25,538 (millions/tonnes), 1,112 (millions/hectares) with its production 253,9 (quintalls/hectares). Factors affecting are last yearâs cassava productivity, its land area, cassava retail price, cassava price, sugar prevenue rice, the worldâs corn price, cornâs land area, last yearâs corn production, cornâs agroindustrial production, cassava price, the end yearâs cassava stock, last yearâs cassava demand, Indonesian import price, last yearâs Indonesia import price, last yearâs cassava price, the worldâs cassava export, Indonesian cassava export and other countriesâ cassava export, the worldâs cassava import, the worldâs import price, world population, Indonesian cassava import, the worldâs cassava import.